Reducing diarrhoea in Guatemalan children: randomized controlled trial of flocculant-disinfectant for drinking-water - Chiller Tom M; Mendoza Carlos E; Lopez M Beatriz; Alvarez Maricruz; Hoekstra Robert M; Keswick Bruce H; Luby Stephen P (The World Health Organization, 2006)
OBJECTIVE: To examine the effect of a new point-of-use treatment for drinking-water, a commercially developed flocculant-disinfectant, on the prevalence of diarrhoea in children. METHODS: We conducted a randomized controlled trial among 514 rural Guatemalan households, divided into 42 neighbourhood clusters, for 13 weeks, from 4 November 2002 through 31 January 2003. Clusters assigned to water treatment with the flocculant-disinfectant were compared with those using their usual water-handling practices. The longitudinal prevalence of diarrhoea was calculated as the proportion of total days with diarrhoea divided by the total number of days of observation. The prevalence of diarrhoea was compared using the Wilcoxon rank-sum test. FINDINGS: The 1702 people in households receiving the disinfectant had a prevalence of diarrhoea that was 40% lower than that among the 1699 people using standard water-handling practices (0.9% versus 1.5%; P = 0.001). In households using the flocculant-disinfectant, children < 1 year of age had a 39% lower prevalence of diarrhoea than those in households using their standard practices (3.7% versus 6.0%; P = 0.005). CONCLUSION: In settings where families rarely treat drinking-water, we introduced a novel flocculant-disinfectant that reduced the longitudinal prevalence of diarrhoea, especially among children aged < 1 year, among whom diarrhoea has been strongly associated with mortality. Successful introduction and use of this product could contribute to preventing diarrhoeal disease globally.